Optimization of Extraction Temperature on The Quality of Alginate from Seaweed Sargassum muticum - Rizqi Wahyu Herdianto; Amir Husni (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Seaweed is one of Indonesia’s marine biological resources which has potential to produce alginate which can be used for food and non-food industries. Several studies had been carried out in an effort to improve the quality of alginate extraction. This study aims to determine the effect of extraction temperature on the quality of sodium alginate from Sargassum muticum. This study used variations in extraction temperatures, namely 30; 40; 50; 60 and 70°C. The parameters observed included yield (%), moisture content (%), ash content (%), pH, whiteness degree and functional groups of alginate. The results showed that the difference in extractiontemperature of sodium alginate had a significant effect on yield and viscosity, but did not significantly affect water content, ash content, and whiteness degree. Extraction temperature of 60°C produced the best yieldand viscosity, 14.90±2.26% and 236.10±36.61 cPs, respectively.